Revitalisasi BUMDes dan Optimalisasi POKDARWIS dalam Hilirisasi Produk Olahan Kopi melalui Revitalisasi Kampung Kopi - Munif, Akhmad; Maesaroh, Dena Ajeng; Indah, Nur; Safira4, Naura; Hidayat, Rana Tahany; Somadani, Mohammad Haykal; Abillah, Shafrie; Nurfauzi, Achmad; Rosyadi, Kinanta Uhail; Setiawan11, Stefanus Ade (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
Sukorejo Village is located in Sumberwringin District, Bondowoso Regency, which is geographically located on the slopes of Mount Ijen. Sukorejo Village contributes to the largest coffee plantation area in Sumberwringin District. The people's extensive coffee land makes it included in the Ijen Geopark (UGG), which is recognized by UNESCO as a heritage site. It seems that the huge potential that already exists in Sukorejo Village has not yet been fully utilized optimally by the local community. This situation reflects the importance of revitalizing BUMDES (Village-Owned Enterprises) and optimizing POKDARWIS (Tourism Awareness Groups) in developing the coffee-based village tourism sector. The activity stages of revitalizing BUMDes include observations and interviews with village structural parties to identify the problem of BUMDes stagnation, then FGD (Focus Group Discussion) to revitalize the problem of BUMDes stagnation and refocus the BUMDes program. Then, carry out socialization on saving 25% of the harvest and the urgency of sachet coffee innovation, then sachet coffee training with BUMDes and termination for discussions regarding the sustainability of the program. Optimizing POKDARWIS began with consolidating the revitalization of coffee villages, training in digital marketing skills, and holding coffee shop and coffee serving creativity competitions. The competition was held to produce a coffee house which also serves as an additional coffee educational tourism destination.